2021
DOI: 10.1186/s12888-021-03323-x
|View full text |Cite
|
Sign up to set email alerts
|

Fear and depression during the COVID-19 outbreak in Cameroon: a nation-wide observational study

Abstract: Background The COVID-19 pandemic has been associated with significant psychological and social distress worldwide. We investigated fear and depression among adults in Cameroon during different phases of the COVID-19 outbreak. Methods An online survey was conducted in Cameroon from June–December 2020 using a structured questionnaire. Socio-demographic data and information regarding COVID-19 history were obtained. Fear and depressive symptoms were as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In China, depression prevalence was higher in urban than rural participants (Gao et al, 2020 ), and in Turkey, depression scores were higher in urban areas and high urbanization was a risk factor for anxiety (Özdin and Bayrak Özdin, 2020 ). In contrast, a study in Cameroon found no association between urbanization, gender, or age on depression and fear during the pandemic but in this sample education level may have been more important (Siewe Fodjo et al, 2021 ). In summary, our results are congruent to Gao et al ( 2020 ) and Özdin and Bayrak Özdin ( 2020 ), which were also conducted during the pandemic, but contrast with pre-pandemic urbanization studies (Shucksmith et al, 2009 ; Purba et al, 2018 ).…”
Section: Discussionmentioning
confidence: 74%
“…In China, depression prevalence was higher in urban than rural participants (Gao et al, 2020 ), and in Turkey, depression scores were higher in urban areas and high urbanization was a risk factor for anxiety (Özdin and Bayrak Özdin, 2020 ). In contrast, a study in Cameroon found no association between urbanization, gender, or age on depression and fear during the pandemic but in this sample education level may have been more important (Siewe Fodjo et al, 2021 ). In summary, our results are congruent to Gao et al ( 2020 ) and Özdin and Bayrak Özdin ( 2020 ), which were also conducted during the pandemic, but contrast with pre-pandemic urbanization studies (Shucksmith et al, 2009 ; Purba et al, 2018 ).…”
Section: Discussionmentioning
confidence: 74%
“…Out of the 32 included studies, the majority were conducted among people living with HIV, [12][13][14][15][16][17][18][19][20][21][22][23][24] followed by students, [25][26][27][28][29][30] hospital patients (including patients with diabetes, cancer and tuberculosis), [31][32][33][34] pregnant and postpartum women, 15 35 36 general population, 37 female sex workers 38 and children 38 39 (online supplemental table 2)…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The prevalence of depressive disorder in the general population ranged from 8.4% 37 measured with Patient Health Questionnaire (PHQ-9) to 18.5% among female community inhabitants measured using the Mini-International Neuropsychiatric 40 Interview.…”
Section: Depressionmentioning
confidence: 99%
“…It is crucial to gather data on the mental health of individuals in the post-infection stage to understand these changes better (2). The social upheaval induced by the pandemic has sparked fear, feelings of isolation, and psychiatric disorders in many individuals (3)(4)(5)(6). The continuing threat of novel viral strains prompts concerns about adverse health outcomes (3).…”
Section: Introductionmentioning
confidence: 99%